Oxysterols as Reliable Markers of Quality and Safety in Cholesterol Containing Food Ingredients and Products - Canzoneri, Federico; Leoni, Valerio; Rosso, Ginevra; Risso, Davide; Menta, Roberto; Poli, Giuseppe (Frontiers in Nutrition, 2022)
Cholesterol is a lipid of high nutritional value that easily undergoes oxidation, through enzymatic and non-enzymatic pathways, leading to a wide variety of cholesterol oxidation products (COPs), more commonly named oxysterols. The major oxysterols found in animal products are 7α-hydroxycholesterol, 7β-hydroxycholesterol, 7-ketocholesterol, 5α,6α-epoxycholesterol, 5β,6β-epoxycholesterol, cholestan-3β,5α,6β-triol, 25-hydroxycholesterol. They are all produced by cholesterol autoxidation, thus belonging to the non-enzymatic oxysterol subfamily, even if 7α-hydroxycholesterol and 25-hydroxycholesterol are in part generated enzymatically as well. A further oxysterol, of full enzymatic origin, has recently been detected for the first time in milk, of both human and bovine origin, namely 27-hydroxycholesterol. Nowadays, gas or liquid chromatography combined to mass spectrometry allows to measure all these oxysterols accurately in raw and in industrially processed food. While non-enzymatic oxysterols often exhibited in vitro relevant cytotoxicity, above all 7β-hydroxycholesterol and 7-ketocholesterol, 27-hydroxycholesterol as well as 25-hydroxycholesterol show a broad spectrum in vitro antiviral activity, inhibition of SARS-CoV-2 included, and might contribute to innate immunity. Quantification of oxysterols was afforded over the years, almost always focused on a few family’s compounds. More comprehensive COPs measurements, also including oxysterols of enzymatic origin are nowadays available, that better display the many advantages of systematically adopting this family of compounds as markers of quality, safety and nutritional value in the selection of ingredients, in processing and storage. Regarding foodstuff shelf-life, COPs monitoring already provided useful hints for more suitable packaging. The identification of a subset of non-enzymatic and enzymatic oxysterols to be routinely assessed in food production and storage is proposed.